A DIMENSIONAL ANALYSIS MODEL FOR THE CALCULATION OF HEAD LOSS DUE TO DISC FILTERS IN DRIP IRRIGATION SYSTEMS1. (10th December 2013) - Wu, Wenyong; Chen, Wei; Liu, Honglu; Yin, Shiyang; Bao, Zhe; Niu, Yong
ABSTRACT In this study, a dimensional analysis model for disc filters was developed based on hydraulic tests of 10 different types of disc filters together with structural parameters such as the inner diameter of the inlet/outlet pipe Db, the outflow path width Pw, outflow path depth Pb, disc width Dd, etc. The correlation coefficient <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghnnq2fxw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Radj2</alternatives> of the model was 0.990. The correlation coefficient between the measured and predicted values of the model was R2 = 0.967. The effects of structural parameter changes on the filter head loss were studied based on the typical physical structural parameters. The inlet/outlet inner diameter was found to have the greatest impact on the head loss. The effects on the head loss resulting from changes in the outflow path width and depth were not significant (P < 0.05). Therefore, when designing the flow path structure of disc filters, the head loss can be effectively minimized by increasing the inlet/outlet inner diameter, inflow path depth, and inner diameter of the disc filter element. In addition, a decrease in the outflow path width and depth can reduce the amount of pollutants entering the flow path without causing a significant increase in the head loss. Copyright © 2013 John Wiley & Sons, Ltd.